Pengaruh Sistem Pendidikan Pesantren Terhadap Pembinaan Moral Santri - Julika Rahma (IAIN Padangsidimpuan, 2021)
This research was conducted using a quantitative approach. Based on the data processing carried out, the pesantren education system is in the